2020
DOI: 10.1177/2631831820937523
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Type of Sexual Dysfunction in Female Patients Receiving Antidepressant Medications

Abstract: Aim: To assess the prevalence and typology of sexual dysfunction in female patients receiving antidepressant medications using the Arizona Sexual Experience Scale (ASEX). Method: A cross-sectional design was employed. A total of 71 married women with various psychiatric disorders receiving antidepressants for at least 3 months’ were evaluated on ASEX, Brief Adherence Rating Scale, Medication Adherence Questionnaire, and Global Assessment of Functioning (GAF) scale. Subjects with a history of sexual dysfunctio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 18 publications
(44 reference statements)
0
7
0
Order By: Relevance
“…Further, it has been reported in previous research that only a handful of patients (13.3%) discussed their SD with their treating psychiatrists. 33 Similarly, in another last work, this proportion was low (14%), which rose to a staggering 58% when doctors actively asked for the information. 35 These findings necessitate an imperative need to evaluate all patients for SD diagnosed with depression on a routine basis.…”
Section: Discussionmentioning
confidence: 92%
See 4 more Smart Citations
“…Further, it has been reported in previous research that only a handful of patients (13.3%) discussed their SD with their treating psychiatrists. 33 Similarly, in another last work, this proportion was low (14%), which rose to a staggering 58% when doctors actively asked for the information. 35 These findings necessitate an imperative need to evaluate all patients for SD diagnosed with depression on a routine basis.…”
Section: Discussionmentioning
confidence: 92%
“…26 Further, studies using ASEX reported the highest prevalence in the sexual aspect of desire or drive (47.9–81.7%), lubrication (35.2–76.05%), achieving satisfaction (18.3–60.56%), and problems in reaching orgasm during sex (18.3–50.7%). 33 Further, 60.56% to 90.1% of the participants reported dysfunction in one of the more sexual domains. 33 These findings are in line with the work of Singh et al 26 who said that women attending general medical clinics said reduced desire (78%), arousal (91%), problems in lubrication (97%), trouble achieving orgasm (87%), issues with pleasure (81%), and pain (64%).…”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations